(untitled) (Revista Innova Educación, 2019)
Social leadership and Christian conception are few topics discussed in the academic world. So, the study on thinking and leadership has as its main objective to determine the influence of the Christian conception on the attitude of social leadership of the students. The type of research is non-experimental descriptive. Due to the nature of the study, the descriptive descriptive design was applied. Also, due to the complexity of the investigation, the analytical and causal design was applied. As a tool, a structured survey was used. This study concludes that the Christian conception negatively influences the attitude of social leadership of students, because the conceptual and practical manifestations in relation to faith, salvation and sin seek passivity, consolidating negative attitudes for the development of social leadership At the same time, be useful to society. This assertion is confirmed by the statistical design applied, Chi square, which was blunt; that is: | 164.6 | > | 8.0 | of level of influence.